If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 3(x + -7) = 6 + -5(x + -9) Reorder the terms: 1 + 3(-7 + x) = 6 + -5(x + -9) 1 + (-7 * 3 + x * 3) = 6 + -5(x + -9) 1 + (-21 + 3x) = 6 + -5(x + -9) Combine like terms: 1 + -21 = -20 -20 + 3x = 6 + -5(x + -9) Reorder the terms: -20 + 3x = 6 + -5(-9 + x) -20 + 3x = 6 + (-9 * -5 + x * -5) -20 + 3x = 6 + (45 + -5x) Combine like terms: 6 + 45 = 51 -20 + 3x = 51 + -5x Solving -20 + 3x = 51 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -20 + 3x + 5x = 51 + -5x + 5x Combine like terms: 3x + 5x = 8x -20 + 8x = 51 + -5x + 5x Combine like terms: -5x + 5x = 0 -20 + 8x = 51 + 0 -20 + 8x = 51 Add '20' to each side of the equation. -20 + 20 + 8x = 51 + 20 Combine like terms: -20 + 20 = 0 0 + 8x = 51 + 20 8x = 51 + 20 Combine like terms: 51 + 20 = 71 8x = 71 Divide each side by '8'. x = 8.875 Simplifying x = 8.875
| xsquared-4=0 | | 5(9-2y)= | | (-9x^4y^4)(0)(-3x^7y)= | | 3x+6x-4=15 | | p-32=58-27 | | 7x-6=5x+18 | | x*x+4=100 | | 20x-3=9x+9 | | z-9/4=3/4 | | -1/5^2 | | -63x=-147 | | 24m-(17m+46)= | | 0=-16x^2+8x+360 | | 9x+13=11x-3 | | 2+u-30=0 | | y=2/3x=2 | | 4k^2-20k-44=0 | | y+3-27=40 | | 3.2b-5.7=201 | | 1.8b+5.2=13.2 | | (8+y)(3y-1)=0 | | 1.8+5.2=13.2 | | 124x/120=6x/120 | | 9x+54=7x+7 | | y+327=40 | | -3-3=50-2 | | f(x)=6x/15x-20 | | 3(2n-3)=15 | | x-60=-2x+21 | | F(x)=6x/9-x | | -6a-5a= | | 4+10x-1=9x+31-6x |